1999
DOI: 10.2307/1161079
|View full text |Cite
|
Sign up to set email alerts
|

Mchape'95, or, the sudden fame of Billy Goodson Chisupe: healing, social memory and the enigma of the public sphere in post-Banda malawi

Abstract: From February to June 1995 approximately 300,000 people attended an anti-AIDS healing cult in Malawi. The name given to the cult was mchape. The article investigates the so-called ‘mchape affair’ and compares it with the anti-witchcraft movements which swept Malawi during the 1930s under the very same name. Against the background of this linguistic identity, the article reflects on the politics of healing, social memory and the public sphere as the national space in which the affair assumed its distinctive sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…For example, in the mid 1990s there were claims that the mchape concoction by a cult leader would cure AIDS (Probst, 1999;Schoffeleers, 1999) and at present chambe and malawix are on the market as AIDS cures. Although some believe in traditional healing to prevent or cure AIDS are evident, many healers, however, say they can do nothing about the disease (Forster, 1998;Ligomeka, 2001).…”
Section: Scientific Validation Of Traditional Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the mid 1990s there were claims that the mchape concoction by a cult leader would cure AIDS (Probst, 1999;Schoffeleers, 1999) and at present chambe and malawix are on the market as AIDS cures. Although some believe in traditional healing to prevent or cure AIDS are evident, many healers, however, say they can do nothing about the disease (Forster, 1998;Ligomeka, 2001).…”
Section: Scientific Validation Of Traditional Medicinementioning
confidence: 99%
“…The elders and traditional healers play an important role in their communities especially in regard to common ailments and mental disorders, and for several of these communities the healers constitute the core of primary health care workers (Bannerman, 1982;Courtright et al, 2000). The popularity of traditional medicine in the treatment of various disease conditions has been widely documented (Brower et al, 1998;Courtright et al, 2000;Kornfield & Namate, 1997;Probst, 1999;Watts, 1989;Zachariah, 2004). For example, in a study by Banerjee (2000), 276 traditional healers saw approximately 4600 patients a week, managing a variety of diseases, mainly of a chronic nature.…”
Section: Introductionmentioning
confidence: 99%
“…No public explanation was offered, but an observer wrote that it was made clear that the emphasis on Chisupe's medicine being a cure only for AIDS and for no other disease was meant to embarrass anyone taking it, as they could no longer hide the fact that they were afraid they were infected, nor could they pretend they were taking it for some other disease. 43 As the leaflet episode illustrates, the government, though making claims to reliance on science and evidence, was either unsure of its own commitments, or too disorganized to project commitments sincerely held to the public.…”
Section: The Storymentioning
confidence: 99%
“…Moreover, he said, even if scientific tests revealed that the substance had curative properties, the government would never acknowledge the results, for fear that their jobs in AIDS bureaucracies would disappear. 46 The rumour mill swung further to Chisupe's side, and the belief that 'Science' was out to steal an 'African' solution became pervasive. 47 Further government efforts to work with Chisupe came to naught.…”
Section: The Storymentioning
confidence: 99%
See 1 more Smart Citation